Cities and agricultural development - Steinhuebel-Rasheed, Linda; Christiaensen, Luc; Minten, Bart; Swinnen, Johan; Vandercasteelen, Joachim (Annual Reviews, 2025)
In recent decades, rapid urbanization in low- and middle-income countries (LMICs) has significantly affected agrifood systems and agricultural development. Innovations in transportation, storage, and value chains, as well as the expansion of nonfarm sectors, have transformed rural communities and reshaped agricultural production patterns. This review revisits the evolving link between cities and agriculture in LMICs, drawing on key theoretical frameworks and recent empirical findings. Three major pathways determining the interaction between urban centers and agricultural development emerge. First, transportation costs and access to urban markets continue to influence agricultural decision-making. Second, changing consumer preferences following urbanization and growing integration into global agrifood value chains drive lasting changes in local farming systems. Third, the expansion of urban nonfarm labor markets is shifting labor away from farms, with uncertain consequences for agricultural development. As a result, the empirical evidence is often context specific.